IMPLEMENTATION OF KNOWLEDGE MANAGEMENT AND TURNOVER INTENTION ON EMPLOYEE PERFORMANCE (HR STUDY ON EMPLOYEES OF CV. CENDEKIA MUDA) - Deddy Novie Citra Arta (JURNAL DARMA AGUNG, 2023)
The purpose of this study is to determine the effect of knowledge management and turnover intention on employee performance. Data collection techniques used were observation, interviews, questionnaires, and literature study. The results of the research on the relationship between knowledge management variables and employee performance is 0.864, the relationship between turnover intention and employee performance is 0.144, and the effect of knowledge management and turnover intention on employee performance is 75.3%. The remaining 24.7% is caused by factors other than this research. The results of the F test calculation obtained F table 50.426 which was calculated at 3.28 indicating knowledge management (X1) and turnover intention (X2) have a significant effect on employee performance (Y).